Book Notes [47, Spring 2001] - Finkel, Alvin (Labour / Le Travail, 2001)
The article briefly reviews "Have Women and Minorities Reached the Top? Diversity in the Power Elite," by Richard L. Zweigenhaft and G. William Domhoff; "An Investigation of Racial Disadvantage," by Derek Leslie et al.; Brian Titley's "The Frontier World of Edgar Dewdney;" Gilbert G. Gonzalez's "Mexican Consuls and Labor Organizing: Imperial Politics in the American Southwest;" Peter Bailey's "Popular Culture and Performance in the Victorian City;" Ching Kwan Lee's "Gender and the South China Miracle: Two Worlds of Factory Women;" Diana Crane's "Fashion and its Social Agendas: Class, Gender, and Identity in Clothing;" "Italian Lives: Cape Breton Memories," edited by Sam Migliore and A. Evo Dipierro; and Glenda Riley's "Women and Nature: Saving the 'Wild' West."